PENGARUH ASPEK RELIGIUSITAS TERHADAP KONSEP MODERASI BERAGAMA PADA MAHASISWA PERGURUAN TINGGI BERBASIS AGAMA DI KOTA KUPANG - Andrian Wira Syahputra; Hendrik A.E Lao (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This study aims to determine the effect of religiosity on the concept of religious moderation in students of Religion-Based Universities in Kupang City. The research method used is a survey method with a quantitative approach, data collection techniques namely observation, questionnaires and documentation. While the data analysis technique used simple regression analysis and the number of samples was 150 students. The results of the study found that the influence of religiosity aspects and the concept of religious moderation in religious-based tertiary institutions in Kupang City had a quite significant influence from the aspect of religiosity on the concept of religious moderation of 33.2% > 5%, which means that Ho is rejected and Ha is accepted. So that the contribution of the aspect of religiosity to the concept of religious moderation is quite influential.